Formation Of Military-Patriotic Feeling in the Education of Young People, Legal Education the Role and Significance of Education (Eurasian Research Bulletin, 2022)
To educate young people in the spirit of military patriotism, to teach them to love their homeland, people and family, to study the great legacy that our patriot grandfathers left before us and to be a worthy successor to them